Use of Geographic Information System (GIS) in Decision Support System for Optimal Location Selection for Opening Ayam Geprek Branch Offices - Prabukusumo, M. Azhar (Jurnal ICT : Information and Communication Technologies, 2024)
Determining the optimal location for opening Ayam Geprek branch offices in Medan City faces complex challenges as it must consider various demographic and economic factors. This research aims to develop a decision support system using Geographic Information System (GIS) that is effective in identifying strategic locations for business expansion. The research method involved analyzing data on population density, accessibility, and culinary competition, which were then integrated in the GIS to generate a map of optimal locations. The results of the analysis showed that the GIS was able to identify several potential locations that met strategic and economic criteria, and had a positive impact on local economic development. The implications of this research show that the use of GIS not only facilitates the business decision-making process, but also contributes to the sustainability and inclusiveness of economic development in the area